Perbedaan Pola Asuh Pada Balita Stunting dan Non Stunting di Provinsi Nusa Tenggara Timur (Analisis Data Riskesdas 2018) - Khuriatun Nabillah; Sri Sumarmi (Universitas Airlangga, 2023)
Background: Over the past decade, NTT has become a province with the highest prevalence of stunting in Indonesia with prevalence exceeding 40%. One of the underlying causes of stunting is inadequate childcare practices. Objectives: This study was aimed to analyze the differences of childcare practices which consisted of early breastfeeding, exclusive breastfeeding, age of introduction of first complementary feeding, immunization status, and weighing between stunted and non-stunted children under five in NTT province. Methods: This study was a quantitative study that used secondary data. The type of study was non-reactive study. The data used comes from 2018 Indonesian Basic Health Research (RISKESDAS). Sub-population observed in this study was 0-59 months old children that live in NTT province. The sample size in this study was 3557 children. Data was statistically analyzed by using Mann-Whitney for the bivariate test and binary logistic regression for the multivariate test. Results: Most toddlers were given IMD (59.3%), not exclusively breastfed (69.9%), given complementary foods at the age of â‰¥ 6 months (64%), given immunizations (86.9%), and weighed (84.8%). Statistical Mann Whitney tests showed that there were differences in exclusive breastfeeding (p=0.001), immunization (p=0.006), weighing (p=0.000), and childcare practices (p=0.001) between stunted and non-stunted children under five in NTT province. However, there was no difference in early breastfeeding (p=0.405) and age of introduction of first complementary feeding (p=0.028) between stunted and non-stunted children under five in NTT province. Through multivariate tests, it was shown that there was a relationship between exclusive breastfeeding (p=0.003), and age of introduction of first complementary feeding (p=0.011) with stunting in NTT province. Conclusions: There were differences in exclusive breastfeeding, immunization and weighing between stunted and non-stunted children under five in NTT province. Exclusive breastfeeding and age of introduction of first complementary feeding are factors that most influence the occurrence of stunting in NTT province.